Investigating TPACK Development among Pre-service Teachers in Micro Teaching in Indonesia - Humaera, Isna; Salija, Kisman; Amin, Fatimah Hidayahni; Nasrullah, Nasrullah; M. Jufrianto, M. Jufrianto; Reskyani, Reskyani (Eastasouth Institute, 2024)
This study explores the development of Technological Pedagogical Content Knowledge (TPACK) among pre-service teachers engaged in micro-teaching sessions in Indonesia. Using quantitative methods, data were collected from 150 pre-service teachers through a structured questionnaire and analyzed using SPSS version 26. The results showed that micro-teaching positively contributed to TPACK development, with significant technological, pedagogical, and content knowledge improvements. The findings confirm the effectiveness of micro-teaching in strengthening TPACK and emphasize the importance of integrating technology-based experiences in teacher education programs. This study provides valuable insights for educators and policymakers aiming to improve pre-service teacher training through practical, technology-supported teaching approaches.